2005
DOI: 10.1097/01.ccm.0000185643.02676.d3
|View full text |Cite
|
Sign up to set email alerts
|

Does the addition of glutamine to enteral feeds affect patient mortality?*

Abstract: The addition of glutamine to standard enteral feeds or to an immunomodulatory formula did not improve outcomes. These findings suggest that enteral glutamine should not be routinely administered to patients with surgical critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 41 publications
(56 reference statements)
1
18
0
5
Order By: Relevance
“…Many studies [4,23,24] and meta-analyses [17,25] of randomized trials suggest that nutritional glutamine supplementation in surgical critically ill patients may be associated with improved survival. Our subgroup meta-analyses suggested that the effect of glutamine supplementation differed by ICU setting.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies [4,23,24] and meta-analyses [17,25] of randomized trials suggest that nutritional glutamine supplementation in surgical critically ill patients may be associated with improved survival. Our subgroup meta-analyses suggested that the effect of glutamine supplementation differed by ICU setting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent Canadian meta-analysis of parenteral glutamine administration in critically ill patients showed a significant benefit for both mortality and infectious complications (39) (www.criticalcarenutrition.com) but could only find a mortality benefit for enteral glutamine in patients with burns and reduced infectious complications in patients with burns or after trauma (37). Since this analysis a further study of enteral glutamine supplementation in patients in a surgical trauma ICU has failed to identify any outcome benefit (40,41).…”
Section: Discussionmentioning
confidence: 90%
“…27 Another study examining the use of enteral glutamine in 185 combined surgical and trauma patients also failed to show differences in mortality, mean number of infections, mechanical ventilation duration, ICU length of stay, and hospital length of stay. 30 In a subgroup analysis of causes of death in all patients, a statistically significant greater percentage of patients (70% vs 25%) who received glutamine supplementation died of sepsis or multiple-organ failure compared with the control group. Similarly, we found a greater occurrence of bloodstream infection with glutamine supplementation.…”
Section: Discussionmentioning
confidence: 93%